Personal Finance and Budgeting Mobile Application, “CashSave” - Wong, Choon Kiat; Mohb Salleh, Mohd Najib (Applied Information Technology And Computer Science, 2023)
Recent studies discovered that there is an increase of interest in personal finance and budgeting as a direct result of the coronavirus pandemic. Therefore, this project aims to provide a platform to aid in their financial management journey by developing an easy-to-use mobile application with an intuitive user interface to bolster their interest and habit in budgeting. The proposed recommender system provides suitable advice and recommendations along with clear visualization of the overall expenditure in the way that are easily manageable by the users. The lack of basic financial education leaves many society fresh comers clueless in managing their money, including credit applying procedure and how to properly manage debt. With this proposed application, it can create an initiative for students and other adults to start their budgeting journey as well as guiding other papers regarding development of mobile application in the field of personal finance and budgeting.